Volume 3: Heat Transfer, Parts a and B 2009
DOI: 10.1115/gt2009-59517
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Flat Plate and Leading Edge Film Cooling

Abstract: This study describes a 3-D computation for film cooling effectiveness investigation using Fluent commercial code, version 6.2. Two configurations are examined: (1) Flat plate, and (2) Semi-cylindrical leading edge with a flat after-body. Three different RANS turbulence models and DES based on Spalart-Allmaras model are utilized to see the difference in accuracy between DES and RANS approaches. Similar to the previous RANS simulation, lateral spreading of film cooling is under-estimated in the RANS simulation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Investigation performed at a single mainstream Reynolds number based on film-hole cylinder diameter of 8,550 at four different blowing ratios which are 1.0, 1.25, 1.5 and 2.0. The result then validated with a journal Numerical Study on Flat Plate and Leading Edge Film Cooling [1].There are a lot of factors that should be considered to increase film cooling effectiveness, such as inclination of the holes that connected with the plenum. Based on Yuen and Martinez-Botas, they reported that there were three angles (30 o , 60 o and 90 o ) have been tested.…”
Section: Introductionmentioning
confidence: 79%
“…Investigation performed at a single mainstream Reynolds number based on film-hole cylinder diameter of 8,550 at four different blowing ratios which are 1.0, 1.25, 1.5 and 2.0. The result then validated with a journal Numerical Study on Flat Plate and Leading Edge Film Cooling [1].There are a lot of factors that should be considered to increase film cooling effectiveness, such as inclination of the holes that connected with the plenum. Based on Yuen and Martinez-Botas, they reported that there were three angles (30 o , 60 o and 90 o ) have been tested.…”
Section: Introductionmentioning
confidence: 79%
“…For example, there are reports on the effects of the density ratio (1) , the blowing angle (2) , and the geometry of injection holes (3) (4) for the film cooling while there are reports on the effects of geometry of turbulence promoters (5) (6) , the passage bend (7) , and the blade rotation (8) for the internal convection cooling. In contrast, studies on the combined effects of the film cooling and the internal convection cooling are rather scarce except for a few studies such as those of Gritsch et al (9) , Fawcett et al (10) Kissel et al (11) , and Sakai et al (12) . The authors showed that the film cooling characteristics are different between the case where the cooling air is supplied from the internal flow and the case where it is supplied from a stagnant plenum.…”
Section: Introductionmentioning
confidence: 92%
“…The authors showed that the film cooling characteristics are different between the case where the cooling air is supplied from the internal flow and the case where it is supplied from a stagnant plenum. Also, Sakai et al (12) showed that the adiabatic film cooling effectiveness varies greatly depending on the Reynolds number of the internal flow. These results suggest a possibility that the film cooling performance can be improved by the optimization of the internal cooling structure.…”
Section: Introductionmentioning
confidence: 99%
“…Большинство исследований систем пленочного охлаждения входной кромки проводились на модели плоской стенки с начальным цилиндрическим участком [1,2]. Такая геометрия обеспечивает близкие к реальным условиям распределения давления и скорости газа (потока) непосредственно в районе входной кромки, однако на плоском участке модели, где происходит релаксация потока, продольные градиенты скоростей и давлений, обусловленные кривизной профиля, отсутствуют.…”
Section: Introductionunclassified